Economy and Society. Chapter II: Sociological Categories of Economic Action - Вебер, Макс (Journal of Economic Sociology, 2010)
We are publishing here the abstract of classical fundamental text, written by Max Weber “Economy and Society”. This is the main part of the Chapter II that covers the basic terms of Weber economic sociology which has not been translated in Russian yet. The translation from German was fulfilled by A. Phillipov, the leading Russian scientist investigating Webers’ publications. It is worth to notice that this translation is special in terms of that it was done very close to the original what led to usage of unusual terms oriented towards the conventional English.